Controle do crescimento e desenvolvimento da batata semente através da condutividade elétrica da solução nutritiva - Coelho, Manuel Benito Novella (2007)
Potato average production in Brazil is well above the world s one, but in Rio Grande do Sul the opposite is true, as this state holds one of the country s smallest mean production. This fact is mainly due to the use of low quality tuber seed. The multiplication of virus-free propagation material, obtained by meristem culture, requires more efficient and economic technologies than the traditional soil-based ones. Various hydroponic systems have been proposed, but all of them stimulate excessive shoot growth. Increasing the salinity of the nutrient solution can reduce the vegetative growth of hydroponic crops, allowing at the same time the use of inferior quality water. The objective of this work was to determine the effect of the saline concentration of the nutrient solution on potato propagation. Two experiments were carried out, using plantlets and minitubers. In the first one, it was determined the effect of multiples of the nutrient solution concentration and in the second one, the effect of NaCl concentrations on plant growth, development and tuber yield. A standard nutrient solution prepared with, in mmol L-1, 13.0 NO3-; 1.5 H2PO4-; 1.5 SO4--; 4.0 Ca++; 6.5 K+ and 1.5 Mg++ was used in both experiments. In the first experiment, this solution was diluted until an electrical conductivity (EC) of 1.0 dS m-1 (T1, control) was reached and the treatments were four additional nutrient solution concentrations, calculated by coefficients of 2.0 (T2), 3.0 (T3), 4.0 (T4) and 5.0 (T5) from T1. Planting was made on March 24th, 2004. At 49 days after planting, mean mass of fresh tubers, shoot and tuber dry mass, tuber/shoot ratio and leaf area index differed from plantlets and minitubers. Plantlets and minitubers can be propagated in low nutrient solution concentrations of electrical conductivity values of 1.0 dS m-1. In the second experiment, the treatments were three salinity levels, reaching electrical conductivities of 2.2 dS m-1 (T1, control, standard nutrient solution without NaCl), 4.2 (T2), 6.2 (T3) and 8.2 dS m-1 (T4). Planting was done on September 24th, 2004, and harvest 62 days later. Tuber/shoot ratio was increased 3 to 4.3 times in plantlets and minitubers, respectively. At high NaCl concentrations plant development is delayed, shoot growth reduced and tuber growth and yield favoured. It was concluded that raising the saline concentration of the nutrient solution through multiple quantities of all the component salts does not increase tuber yield and has no effect on tuber/shoot ratio. By using NaCl, shoot growth is comparatively more reduced than that of minitubers, so it can be a management practice to reduce leaf expansion and nutrient solution use.